2007
DOI: 10.3174/ajnr.a0739
|View full text |Cite
|
Sign up to set email alerts
|

The Pathophysiology of Idiopathic Normal Pressure Hydrocephalus: Cerebral Ischemia or Altered Venous Hemodynamics?

Abstract: BACKGROUND AND PURPOSE:Many theories of normal pressure hydrocephalus (NPH) stress the importance of ischemia in the deep white matter. Alternate theories stress a reduction in superficial venous compliance and changes in pulse-wave propagation. An overlap in the cerebral blood flow volumes measured between NPH and controls suggests that ischemia may not be a prerequisite for this condition. This study sought to compare blood flow and compliance measures in a cohort of patients with NPH selected for having art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
99
1
22

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(126 citation statements)
references
References 41 publications
4
99
1
22
Order By: Relevance
“…⌬V ART and ⌬V SC can be measured with PC-MR imaging. 10,12 Moreover, the difference between the arterial volume increase and the volume shifted to the spinal compartment is the ⌬V IC . It follows that PC-MR imaging and lumbar CSF infusion measurements can be combined to calculate PVI CC , PVI IC , and PVI SC .…”
Section: Methodsmentioning
confidence: 99%
“…⌬V ART and ⌬V SC can be measured with PC-MR imaging. 10,12 Moreover, the difference between the arterial volume increase and the volume shifted to the spinal compartment is the ⌬V IC . It follows that PC-MR imaging and lumbar CSF infusion measurements can be combined to calculate PVI CC , PVI IC , and PVI SC .…”
Section: Methodsmentioning
confidence: 99%
“…9) On the other hand, an overlap in the CBF volumes measured between patients with NPH and normal subjects suggested that ischemia may not be a prerequisite for this condition, but instead may reflect increased superficial venous pressure in patients with NPH. 1) Cerebral circulatory disorders in patients with NPH can manifest as either of two pathophysiological conditions: circulatory disorder of the cerebral cortical region, and that of the thalamus-basal ganglia region, and various patterns may develop according to the disease stage. 15) Such discrepant explanations may derive from the absence of comprehensive understanding of NPH, which is actually a dynamic and divergent disease in Neurol Med Chir (Tokyo) 48, October, 2008 S. Tsutsumi et al…”
Section: Discussionmentioning
confidence: 99%
“…Sowohl die intrakraniellen Binnenbewegungen des Liquors als auch die Nettovolumenschwankungen der drei Kompartimente Parenchym, Blut und Zerebrospinalflüssig-keit waren nun einer Auflösung innerhalb einer einzelnen Herzaktion zugänglich. Wegweisende Messungen führten Greitz [12] und Bateman [13][14][15][16][17] durch und entwickelten ein Verständnis der Pathophysiologie des Normaldruckhydrozephalus, dessen pathogenetischen Ausgangspunkt eine herabgesetzte Compliance der zerebralen Blutgefässe bildet. Die physiologische Blutversorgung des Gehirns beginnt mit einem pulswellenartigen Blutstrom im Bereich der grossen Hirnbasisarterien und der subarachnoidal verlaufenden Arterien.…”
Section: Pulswellen Und Magnetresonanztomografieunclassified
“…Daraus folgt eine minimale systolische Volumenzunahme des Hirnparenchyms unter physiologischen Bedingungen. Dies äussert sich in der minimalen systolischen Liquorauslagerung über das Aquädukt, die unter physiologischen Bedingungen nur 30 µl beträgt [12,16].…”
Section: Pulswellen Und Magnetresonanztomografieunclassified